Basic epidemiologic model SIR for COVID-19: case of Peruvian Regions - Vergara Moreno, Edmundo (2020)
In this work, a basic epidemiological model is used to determine the evolution of COVID-19 in each of the regions of Peru. For determining the parameters of the model which characterize a certain epidemic, the reports of infected, deceased and recovered people provided by the Regional Health Management of Peru are used. As a result, we obtained the configuration of the infected, susceptible and removed which are consistent with the existing bibliography, thus we also obtain a time interval in which there is a considerable number of infected, the maximum number of infected and the date on which it occurs.